THE ORGANIZATION OF WORK OF STOROZHISHCHENSKY CORRECTIVE COLONY SHELTER OF THE SMOLENSK PROVINCE IN THE CONTEXT OF I.F. GERBART'S IDEAS - Kozhemyakina, Elena; Senchenkov, Nikolay (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
In article the organization of teaching and educational work of Storozhishchensky corrective colony shelter of the Smolensk province opened in 1894 in the context of the ideas of the outstanding German scientist-teacher Johann Friedrich Gerbart is considered. The analysis of labor, religious and moral, physical, esthetic training of children of colony of a shelter taking into account psychology and pedagogical installations of Gerbart is given. Authors have presented experiment of colony shelter on training of pupils for independent life in society. In work also teaching and educational work of the agricultural lowest school of the 1st category opened at colony shelter is also analysed. At this school labor education of the children who are in colony shelter was carried out. Here pupils acquired knowledge, abilities and skills necessary for them for further life in society. In article the mode, training programs, methods, forms and means of labor education at agricultural lowest school of the 1st category in detail reveal.